Understanding the influence of customers on product innovation. (1st January 2014) - Chang, Danni; Chen, Chun-Hsien
In this article, the influence of customers on product innovation is examined through a hypothesis testing study. Based on an analysis of relevant research, two hypotheses are developed: H1, customers are not the most significant factor positively affecting product innovation in new product development (NPD); and H2, customers have curved effects on product innovation in NPD. To test the hypotheses, an interactive multiple regression model and a curve fitting model are developed respectively. The simulation results showed that the most significant positive influence on product innovation results is made by external resources such as ' consultants, commercial lab or private R&D institutions '. Moreover, different amounts of input information provided by customers/clients/end-users have curved impacts on innovation results. It is suggested that firms should properly allocate their research focus on customers and other important factors. Moreover, it may be a promising way to improve product innovation through seeking support from external resources.